Scheduled Waste Inventory And Monitoring System - Nur Afiqah, Mohammed Jamil (2023)
With the rapid development of the technology nowadays, the company has to start using an online system in order to ease them and make it efficient to handle the company information and be able to store it safely. However, the Flexsys Chemical (M) Sdn Bhd is still keeping the record of scheduled waste manually. This process can be unsystematic and inconvenient for the staff to keep doing that. Hence, the development of the Scheduled Waste Inventory and Monitoring system will make a change for the staff as it will improve the process of keeping the scheduled waste information and the manager is able to remotely monitor the disposal of scheduled waste. That was the objective of the project. The systems will provide few features that can help the staff to be able to complete their work in a very efficient way. In fact, the system also can be used by other companies if the company uses the same method to store and monitor their waste. The Scheduled Waste Inventory and Monitoring system will be developed by using the agile methodology as it is easy to develop the project and make any changes according to the client preferences if any during the development process. The system will be tested by one of the staff from Flexsys Chemical (M) Sdn Bhd in order to prove that the system already meets the users’ requirements.